Parental knowledge, attitudes, and practices on probiotic use in preschool children in Serbia: a cross-sectional study - Đanić, Maja; Pavlović, Nebojša; Ostojić, Tijana; Marković, Nikolija; Stanimirov, Bojan; Lazarević, Slavica; Mikov, Momir (Frontiers in Immunology, 2025)
IntroductionConsidering the crucial role of the gut microbiome in children’s immunity and overall health, there is increasing interest in the use of probiotics for children. Insufficient parental awareness may result in the underuse of probiotics in appropriate clinical situations, improper strain selection, incorrect therapy duration, and overlooking potential drug interactions, all of which can undermine their efficacy and safety. Therefore, this study aimed to assess parents’ knowledge, attitudes, and practices regarding probiotic use in preschool-aged children in Serbia, along with the factors influencing these aspects.Materials and methodsThe study was conducted using an anonymous electronic survey distributed via social media to parents of children aged 1–7 years in Serbia. A binary logistic regression model was used to analyze the factors associated with parental knowledge and attitudes toward probiotic use.ResultsThe study included 1,625 parents. The median knowledge score of all respondents was 7.0 (interquartile range [IQR]: 6–8), while the median attitude score was 26.0 (IQR: 23–29), based on their respective scales (0–10 for knowledge and 7–35 for attitude) with significant differences (p < 0.001) between parents who used probiotics for their preschool children in the past year (62.5%) and those who did not (37.5%). The most common indications for probiotic use were alongside antibiotic therapy reported by 75.2% of parents, and for gastrointestinal issues, stated by 69.3% of parents. Parents showed the least knowledge about the strain-specific effects of probiotics and their interactions with medications. Although overall attitudes were moderately positive, approximately 50% of parents expressed doubts about probiotic efficacy. Logistic regression analysis revealed that higher parental education, occupation related to health care, longer duration of probiotic use, and consideration of probiotic strain selection significantly increased the odds of having adequate knowledge and a positive attitude toward probiotics.ConclusionThe study revealed that the majority of parents lack adequate knowledge about probiotics and exhibit some skepticism regarding their effectiveness, which is reflected in their practical use for their children. Therefore, the role of healthcare professionals and pediatricians is crucial in educating parents about probiotics, offering guidance on their benefits, proper usage, and the selection of the most appropriate products.